Prevention-educational work in the Prosecutor’s Office (psychological-the legal aspect) - Озерський, Ігор Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article is about directions of preventive and educational work of the Prosecutor’s Office’s personnel departments from a psychological and law positions. The issues of adoption of the Professional Prosecutors and Investigators’ Code of Ethics are considered.